Electron microscopy of polymers - Michler, Goerg H (Springer, 2017)
A study of polymers using Electron Microscopy(EM) necessitates special techniques, precautions and preparation methods, including ultramicrotomy. This book discusses the general characteristics of the various techniques of EM, including scanning force microscopy (AFM). It also presents examples from various classes of polymers.